2017
DOI: 10.2147/prom.s117549
|View full text |Cite
|
Sign up to set email alerts
|

Non-valvular atrial fibrillation: impact of apixaban on patient outcomes

Abstract: Atrial fibrillation is the most common arrhythmia worldwide, and carries a significantly increased risk of thromboembolic stroke. Initially, vitamin K antagonists were used as stroke prophylaxis; but more recently, a group of drugs known as novel oral anticoagulants have been developed. Apixaban belongs to this group of drugs, and is a factor Xa inhibitor that has emerged as a popular pharmacological agent worldwide. In this review, we will provide an overview of the pivotal trials in the development of apixab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Furthermore, studies suggested that off‐label underdosing of apixaban without following the dose‐reduction criteria is associated with a nearly 5‐fold increased risk of stroke . An important result from Ioannou et al is that using a reduced dose of apixaban in patients with normal renal function and younger than 75 years was associated with 50% lower plasma concentrations than when treated with standard dose. This can lead to subtherapeutic apixaban plasma levels and predisposes those patients to a higher risk of developing thromboembolic events.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies suggested that off‐label underdosing of apixaban without following the dose‐reduction criteria is associated with a nearly 5‐fold increased risk of stroke . An important result from Ioannou et al is that using a reduced dose of apixaban in patients with normal renal function and younger than 75 years was associated with 50% lower plasma concentrations than when treated with standard dose. This can lead to subtherapeutic apixaban plasma levels and predisposes those patients to a higher risk of developing thromboembolic events.…”
Section: Resultsmentioning
confidence: 99%
“…However, this can be explained, in part, by clinicians not always prescribing according to the guidelines, introducing this reduced‐dose regimen in patients who should be receiving the standard dose. Therefore, these patients become unintentionally undertreated, which increases their risk of thromboembolic complications . Underdosing may have important implications, as rates of systemic embolism, stroke, major bleeding and mortality are generally higher for patients receiving the lower vs higher DOAC dose .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probably because off-label underdosing of apixaban may lead to subtherapeutic plasma level of apixaban, potentially resulting in a higher incidence of subclinical stroke and long-term mortality. 31 As such, the description of the off-label underdose of apixaban should not be in the recommendation. When patients are not up to the standard of on-label reduced dose, sticking to the on-label dose of apixaban would let patients benefit more from it.…”
Section: Studymentioning
confidence: 99%
“…In contrast to monogenic inherited cardiomyopathies, AF is a complex heart rhythm disorder caused by environmental and multi-genic risk factors [ 39 ] and significantly increases the risk for stroke and heart failure. Apixaban is an anticoagulant drug used to reduce the risk for stroke in patients with non-valvular AF [ 40 ]. The work of Rosian et al showed that there was no significant association between peak apixaban plasma concentrations in patients with specific SNPs in the ABCB1 gene, encoding an ATP-binding cassette (ABC) transporter [ 41 ].…”
mentioning
confidence: 99%